Effects of PPARγ Ligands on Leukemia. (21st May 2012) - Tabe, Yoko; Konopleva, Marina; Andreeff, Michael; Ohsaka, Akimichi
Abstract : Peroxisome proliferator-activated receptors (PPARs) and retinoic acid receptors (RARs), members of the nuclear receptor superfamily, are transcription factors that regulate a variety of important cellular functions. PPARs form heterodimers retinoid X receptor (RXR), an obligate heterodimeric partner for other nuclear receptors. Several novel links between retinoid metabolism and PPAR responses have been identified, and activation of PPAR/RXR expression has been shown to increase response to retinoids. PPAR γ has emerged as a key regulator of cell growth and survival, whose activity is modulated by a number of synthetic and natural ligands. While clinical trials in cancer patients with thiazolidinediones (TZD) have been disappointing, novel structurally different PPAR γ ligands, including triterpenoids, have entered clinical arena as therapeutic agents for epithelial and hematopoietic malignancies. Here we shall review the antitumor advances of PPAR γ, alone and in combination with RAR α ligands in control of cell proliferation, differentiation, and apoptosis and their potential therapeutic applications in hematological malignancies.